Unlocking African economic growth potentials through the lenses of trade openness and financial development shocks - Abdussalam Aljadani; Ridwan Lanre Ibrahim; Lukman Raimi; Usama Al-Mulali; Mamdouh Abdulaziz Saleh Al-Faryan (Cogent Economics & Finance)
The African continent is advancing toward the ambitious objectives of Vision 2063, which outlines a sustainable and prosperous future, but progress depends on targeted macroeconomic policies, particularly in trade. However, inadequate financing remains a key obstacle to realizing the full benefits of trade. Our research examines the impact of trade openness and the asymmetric effects of financial development on economic growth (EG) in Africa's leading financially developed nations—South Africa, Egypt, Morocco, Nigeria, and Algeria—over the period 1995–2020. Using robust methodologies such as the Pooled Mean Group (PMG) and Quantile Regression (QR), we find that trade openness is a critical driver of EG. Positive shocks in financial development enhance growth, while negative shocks hinder it. Additionally, digitalization and market size foster EG, whereas underdeveloped transport services constrain it. These findings highlight the need for policies that promote trade openness, mitigate financial instability, leverage digitalization, expand market size, and improve transport infrastructure to advance the goals of Vision 2063.